2023
DOI: 10.15252/emmm.202217101
|View full text |Cite
|
Sign up to set email alerts
|

Axin2 coupled excessive Wnt‐glycolysis signaling mediates social defect in autism spectrum disorders

Abstract: Social dysfunction is the core syndrome of autism spectrum disorder (ASD) and lacks effective medicine. Although numerous risk genes and relevant environmental factors have been identified, the convergent molecular mechanism underlying ASD‐associated social dysfunction remains largely elusive. Here, we report aberrant activation of canonical Wnt signaling and increased glycolysis in the anterior cingulate cortex (ACC, a key brain region of social function) of two ASD mouse models (Shank3−/− and valproic acid‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…For example, it has been reported that ENO1 interacts with hepatocyte growth factor receptor (HGFR) and activates HGFR and Wnt signaling via increased phosphorylation of HGFR and the Wnt co‐receptor low‐density lipoprotein receptor‐related protein 5 and 6 26 . Additionally, Axin2, a key inhibitory molecule in Wnt signaling, interacts with the ENO1 in neurons of autism spectrum disorders 27 . Furthermore, SFRPs are among the most studied Wnt inhibitors 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been reported that ENO1 interacts with hepatocyte growth factor receptor (HGFR) and activates HGFR and Wnt signaling via increased phosphorylation of HGFR and the Wnt co‐receptor low‐density lipoprotein receptor‐related protein 5 and 6 26 . Additionally, Axin2, a key inhibitory molecule in Wnt signaling, interacts with the ENO1 in neurons of autism spectrum disorders 27 . Furthermore, SFRPs are among the most studied Wnt inhibitors 28 .…”
Section: Discussionmentioning
confidence: 99%
“…26 Additionally, Axin2, a key inhibitory molecule in Wnt signaling, interacts with the ENO1 in neurons of autism spectrum disorders. 27 Furthermore, SFRPs are among the most studied Wnt inhibitors. 28 Research has shown that the expression of βcatenin was significantly decreased at both the mRNA and protein levels in the villi and decidua of the recurrent spontaneous abortion group compared with the normal control group.…”
Section: Discussionmentioning
confidence: 99%